Implementasi Pembelajaran IPS Berbasis Multikultural dalam Mengatasi Sikap Intoleransi pada Siswa - Rahma Laila Azahra; Siti Ekowati Rusdini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Intolerance among students is a social problem that needs serious attention in social studies education, given that social studies plays a strategic role in shaping students' social attitudes and character. Differences in cultural, religious, and social backgrounds that are not properly managed have the potential to cause intolerant attitudes in the school environment. The research was conducted at SMP N 11 Semarang. This study aims to determine how multicultural-based social studies learning can be implemented to overcome intolerance among students and serve as a basis for the development and innovation of multicultural learning in schools. The research method used is qualitative with the Milles and Huberman interactive data analysis model, which includes data reduction, data presentation, and conclusion drawing. Data collection techniques were carried out through observation, interviews, and documentation. The research analysis referred to James A. Banks' theory of The Dimensions of Multicultural Education. The results showed that multicultural-based social studies learning was implemented through materials covering multicultural education, such as population dynamics, the use of student project-based learning methods, and learning media in the form of interactive videos and folk tales. The application of these multicultural dimensions played a role in increasing mutual respect, reducing prejudice, and developing awareness of differences in background. The conclusion of this study shows that multicultural-based social studies learning can overcome intolerance among students and can be used as a basis for developing innovations in social studies learning oriented towards multicultural education. Keywords: Student Intolerance, Multiculturalism, Social Studies Learning, Multicultural Education, Tolerance